1985
DOI: 10.1073/pnas.82.9.2799
|View full text |Cite
|
Sign up to set email alerts
|

α-Amanitin resistance is developmentally regulated in carrot

Abstract: Carrot cells are capable of inactivating aamanitin only in embryogenic conditions (regenerating cells and embryoids). Instead, the mutant line a3 is capable of inactivating the drug also in nonembryogenic conditions (vegetative growth). The mutation is dominant in somatic hybrids and is pleiotropic, allowing expression during vegetative growth of other embryonal functions. The inactivation of a-amanitin is due to the oxidative activity of tyrosinase.Research on plant development is much less advanced a field t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…It is possible, but unlikely, that inactivation of ␣-amanitin occurs during development in the male gametophytes of M. vestita. In some carrot suspension culture cell lines, ␣-amanitin can be inactivated by tyrosinase activity (Pitto et al, 1985). Since we have not directly assayed for tyrosinase activity, we are unable to rule out the possibility of ␣-amanitin inactivation in M. vestita.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, but unlikely, that inactivation of ␣-amanitin occurs during development in the male gametophytes of M. vestita. In some carrot suspension culture cell lines, ␣-amanitin can be inactivated by tyrosinase activity (Pitto et al, 1985). Since we have not directly assayed for tyrosinase activity, we are unable to rule out the possibility of ␣-amanitin inactivation in M. vestita.…”
Section: Discussionmentioning
confidence: 99%
“…However, α-amanitin has not been successfully used in plant MZT experiments, possibly because the drug lacks useful effects on plant embryos. Early pioneering work in Daucus carota showed that carrot cells inactivate α-amanitin under embryonic conditions (Pitto, Schiavo, & Terzi, 1985). Two other inhibitors, actinomycin D and cordycepin, have been used in N. tabacum MZT experiments.…”
Section: Timing Of the Mzt In Higher Plantsmentioning
confidence: 99%
“…The mechanism for this inactivation has not been clarified, although the enzyme tyrosinase (phenoloxidase) has been proposed as responsible for degradation of a-amanitin since high activity of this enzyme was observed exclusively during embryogenesis in these carrot strains (14).…”
Section: Introductionmentioning
confidence: 99%
“…During embryo formation some carrot strains have the ability to inactivate the fungal toxins cycloheximide (22) and a-amanitin (14) supplied to the culture medium. The mechanism for this inactivation has not been clarified, although the enzyme tyrosinase (phenoloxidase) has been proposed as responsible for degradation of a-amanitin since high activity of this enzyme was observed exclusively during embryogenesis in these carrot strains (14).…”
mentioning
confidence: 99%